IMPLIKASI TEORI BELAJAR BEHAVIORISTIK PADA SISWA - Maghfirah Insannia; Assa Dullah Rouf; Hidayani Syam (ADIBA : JOURNAL OF EDUCATION, 2024)
The learning process carried out by a person will definitely show different symptoms or processes and learning outcomes. This difference originates from the fact that humans have different abilities in understanding things. So, a person's success in learning is a combination of his ability based on his potential to understand something, appropriate learning, and good teaching and learning methods. These factors are divided into external factors and internal factors. Internal factors are factors that come from within the student, which include: talents, interests, motivation, attitudes, learning styles and others. External factors are factors that come from outside the student, which include: teaching methods, evaluation tools, learning environment, teaching media, etc. The research for writing this article used the literature study method. Literature study is the process of collecting data by collecting library data, namely library literature from books, articles and journals. In this research the author uses a critical descriptive approach by prioritizing analysis of data sources. The data source for this article comes from several articles or journals written by educational experts who have experience.